Reference values for the 6-min walk test in healthy subjects 20–50 years old - Chetta, Alfredo; Zanini, Andrea; Pisi, Giovanna; Aiello, Marina; Tzani, Panagiota; Neri, Margherita; Olivieri, Dario (Respiratory medicine, 2006)
In 102 healthy Caucasians, 20–50 years old, we investigated the effect of anthropometrics on the 6-min walk test (6MWT), in order to provide reference values for walk distance (6MWD), oxygen saturation (SpO 2), pulse rate (PR), respiratory rate (RR), breathlessness perception (VAS) and for the walking distance and body weight product ( DW). The mean 6MWD and DW values were 593±57 and 638±44 m ( P<0.01) and 35,030±5306 and 48,882±6555 kg m ( P<0.01), respectively for women and for men. While walking, SpO 2 remained unaltered and subjects reached 67±10% of their maximal predicted heart rate and a RR mean value of 19±4 bpm. VAS ratings were significantly higher in females as compared to males (24±15 vs. 18±5 mm, P<0.05), however, when corrected for PR change while walking, they were not different. The equation by stepwise multiple regression analysis included height, age and gender for the 6MWD and accounted for 42% of the total variance. This study confirms the relevant effect of anthropometrics on walking capacity and suggests that when rating dyspnea, the change in heart rate during walking should be considered.